2014
DOI: 10.1007/s00402-014-2028-2
|View full text |Cite
|
Sign up to set email alerts
|

Does immobilization after arthroscopic rotator cuff repair increase tendon healing? A systematic review and meta-analysis

Abstract: Level II; systematic review of levels I and II studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…For instance, Chan et al 16 found no differences between groups for all aforementioned outcomes, which was similar to the founds from Littlewood et al 17. In contrast, the reviews from Chang et al ,18 Huang et al ,20 Riboh and Garrigues21 and Shen et al 15 found differences for ROM which favours the early management, especially of shoulder flexion.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…For instance, Chan et al 16 found no differences between groups for all aforementioned outcomes, which was similar to the founds from Littlewood et al 17. In contrast, the reviews from Chang et al ,18 Huang et al ,20 Riboh and Garrigues21 and Shen et al 15 found differences for ROM which favours the early management, especially of shoulder flexion.…”
Section: Resultssupporting
confidence: 53%
“…These were: van der Meijden et al ,12 as the primary objective was not to compare the influence of the rehabilitation time during the recovery process; Ross et al ,13 which used a non-systematic review method and Shen et al ,14 which was published in Chinese. It is noteworthy that another review from Shen et al ,15 in the same topic, was published in English in the same year, which might indicate that the same review has been published in two different journals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel dazu erfolgt eine progrediente passive Mobilisierung, die in Zusammenschau der Studienlage risikoärmer und daher empfehlenswerter zu sein scheint als eine frühe aktive Mobilisation [8,19,22,29].…”
Section: Dauer Der Immobilisationunclassified